5 degree of freedom robotic Arm - Iqbal, Md. Rashed; Aysha, Umme; Robyat, Tanjila (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.